UU 13 Tahun 2003, Investasi Dan Kesempatan Kerja - Henriko Tobing (Jurnal Ketenagakerjaan, 2017)
This study attempts to analyze the impact of Law 13 of 2003 on employment for investment and employment creation. This study is expected to provide information on how the position of these provisions of the law amid efforts to increase investment and job creation. The analytical method uses a quantitative approach using three statistical analysis tools. Data obtained from various sources both literature and online media. The blade ofstatistical analysis using multivariate analysis model Anova (Manova), multiple linear regression and Pearson correlation with several variables that are considered to influence job opportunities including qualitative variable UU13 year 2003 as the key variable that want to be seen from this research. Of the three models, the results of the analysis are mutually reinforcing which indicates that employment opportunities are influenced by the existence ofLaw 13 of 2003, through the Manova approach, the provisions of this law affect both formal and informal sector positively but this provision does not significantly affect investment both domestic and foreign investment. Using Pearson's correlation results also show a significant positive effect and a very strong relationship between the decency of legislation and employment but not with investment. Other results by using regression analysis obtained that all variables namely economic growth, investment, interest rates and regulation have a significant effect on employment.